PENGARUH PEMBELAJARAN AKTIF DENGAN METODE PENCARIAN INFORMASI TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN BARIANG RAO-RAO MUARALABUH KAB. SOLOK SELATAN - Wahyuni, Sisri - (STKIP PGRI Sumbar, 2014)
This study originated from the fact that the school students understanding of mathematical concepts is still low. This study aims to determine how the development and understanding of the concept of student activities. This research includes the design of the random experiment research on the subject. The population in this study were eighth grade students MTsN Bariang Rao-Rao Muaralabuh The research uses a technique of random sampling, The instrument used is the final test. The results of the analysis of activity observation sheet can be concluded that the activity increase at each meeting. Based on the results of the analysis of the final test students understanding of mathematical concepts experimental class higher than the control class. Hypothesis testing using the U Mann-Witney test with the help of MINITAB software. It can be concluded that the students understanding of mathematical concepts to the application of information retrieval methods lebik good of the students understanding of mathematical concepts with the application of conventional learning eighth grade students MTsN Bariang Rao-Rao Muaralabuh